Thermomechanical and structural analysis of green hybrid composites based on polylactic acid/biochar/treated W. filifera palm fibers - Lekrine, Abdelaziz; Belaadi, Ahmed; Dembri, Isma; Jawaid, Mohammad; Ismail, Ahmad Safwan; Abdullah, Mahmood M.S.; Chai, Boon Xian; Al-Khawlani, Amar; Ghernaout, Djamel (Elsevier, 2024)
The purpose of this study is to investigate the chemical treatment impact on Washingtonia filifera (WF) fibers using sodium bicarbonate (10% NaHCO3) for varying durations (24, 48, 72, 120, and 168 h) on the physical and mechanical characteristics of polylactic acid (PLA)/WF-biochar/biomass hybrid biocomposites. Differential scanning calorimetry, thermogravimetric analysis, and Fourier transform infrared spectroscopy were employed to examine the temperature effect on the mineralogical composition of treated and raw WF fibers and monitor their thermal behavior. The produced biocomposites' tensile, impact, flexural, and morphological characteristics were evaluated. The results demonstrate that chemical treatments improve matrix-fiber adhesion and remove impurities from the fiber surface. Hybrid biocomposites of PLA biopolymers manufactured from biochar and WF fibers given a sodium bicarbonate treatment for 72 h exhibit improved mechanical properties, such as elasticity modulus and strength under tensile and flexural forces. Consequently, these new hybrid biocomposites can be used in various structural and non-structural products, such as car interiors, new 3D printer filament, biomedical equipment and materials, sports equipment, food packaging.